“I’ve adopted it as my smell”: transgender identity and the olfactory - Easterbrook-Smith G (Taylor and Francis Group, 2025)
Smell is an often-overlooked sense within transgender studies, despite the extensive theorization of the ways that scent and perfume is categorized along gendered lines, and its links to identity more broadly. This article begins to address this presently under-studied topic, drawing on data from 26 interviews with transgender people about their perspectives on smell, scent, and fragrance in relation to identity. Interview data was analyzed using a combination of thematic and critical discourse analysis approaches. The participants reported that smell was often a central component of early experiences which prompted them to explore or question their gender identity; that fragranced items were something which they used to affirm their gender personally; and that smell was something they used to manage or direct others’ perceptions of their identity, including to minimize experiences of misgendering. Participants were acutely aware of how fragrances are culturally “read” as gendered, and while they were often critical of these divisions, they also acknowledged they could be useful at times. It is evident that smell and fragrance can form part of the process of gender identity exploration and expression for transgender people.
Keywords: Transgender studies; gender identity; fragrance; smell; identity construction; gender affirmation